(untitled) (New Delhi, 2005)
India hardly regarded the countries of Southeast Asia and South Pacific as priority areas despite the latterÃs cultural, political, economic and strategic significance. The long spell of mutual alienation understandably gave way to mutual distrust and suspicion. This dark period in IndiaÃs relations with the countries of Southeast Asia and South Pacific was, however, brought to an end following the reshaping and reorientation of IndiaÃs foreign policy, manifest in the vigorous pursuit of ëLook EastÃ policy since the last decade of the previous century. Positive factors such as the pursuit of ASEAN and AustraliaÃs ëLook WestÃ policy coinciding with the adoption of ëLook EastÃ policy by India, had already registered impressive progress in the field of economy, strategy and cultural relations between India and ASEAN. The leading specialists have critically examined the fruitful synergy in the relations between India and the countries of Southeast Asia and South Pacific.
Keywords: Southeast Asia,Ấn Độ,Đông Nam Á,India; Foreign relations,Quan hệ ngoại giao,Quan hệ ngoại giao,Foreign relations; India,Đông Nam Á,Ấn Độ,Southeast Asia